Mélange versus forearc contributions to sedimentation and uplift, during rapid denudation of a young Banda forearc-continent collisional belt. (1st May 2017) - Duffy, Brendan; Kalansky, Julie; Bassett, Kari; Harris, Ron; Quigley, Mark; van Hinsbergen, Douwe J.J.; Strachan, Lorna J.; Rosenthal, Yair
Graphical abstract: Highlights: We provide the first provenance analysis of synorogenic sediments from Timor. Reworked mélange dominates early sediments, and all mud sedimentation. Coarse sediments were sourced from the resistant overthrust Banda Terrane rocks. Exhumation of resistant rocks from under mélange enhanced rapid uplift. Re-dated DSDP262 stratigraphy consistent with synchronous collision across Timor. Abstract: New sedimentary geochemistry and petrographic analyses provide the most extensive sedimentary documentation yet of the rapid denudation of the young Timor orogen. The data from three basins including two widely-separated, well-dated sections of the Synorogenic Megasequence of Timor-Leste, and a re-dated DSDP 262, constrain the source and timing of detrital sediment flux during forearc-continent collision along the Timor sector of the Banda Arc. The exhumed synorogenic piggy-back basins formed above a mélange unit that developed at the expense of a weak stratigraphic horizon in the Mesozoic stratigraphy, and was exhumed to the sea floor in latest Messinian time. Following an interval of deep marine chalky marl sedimentation, an increasingly muddy sediment flux indicates that the island of Timor became emergent and shed sediment by 4.5 Ma. Comparison of exhumed sections with similar patterns in the DSDP262 chemistry suggests that the sediment source was probably located some 50–60 km distant from the basin, which is consistent with the Aileu region of Timor-Leste that shows an appropriate exhumation history. All sedimentation between 4.5 and 3.2 Ma was probably derived from a low-relief, rapidly eroding, and mudstone-dominated landscape with geochemical affinities to the Triassic-mudstone-derived synorogenic mélange. The mélange unit overlies and surrounds the Banda Terrane, and was presumably structurally emplaced by propagation of a decollement through the Triassic rocks during the collision. After 3.2 Ma, sedimentation was dominated by hard rock lithologies of the Banda Terrane, consisting of forearc cover and basement, the latter including elements of metamafic rocks and metapelites. This phase of sedimentation was accompanied by rapid uplift, which may have been partly driven by a transient imbalance between rock uplift and denudation as resistant lithologies emerged from below mélange-like mudstone. Previous work has suggested that the timing of collision in Timor-Leste and West Timor was substantially different. Our reevaluation of DSDP 262 facies migration history in the context of the re-dating presented here, favours a relatively synchronous onset of uplift in both halves of the island, but with different partitioning of strain between the foreland and hinterland in each half of the island.